Longitudinal Tau Accumulation and Atrophy in Aging and Alzheimer Disease - Harrison, Theresa M. (Ann Neurol, 2019)
OBJECTIVE: To determine the rate of tau accumulation in healthy older adults (OA) and patients with Alzheimer disease (AD), as well as the relationship of tau accumulation to cortical atrophy. METHODS: Two longitudinal flortaucipir (FTP) positron emission tomography (PET) and magnetic resonance imaging (MRI) scans were acquired from 42 OA (21 Pittsburg compound B [PiB](+), age = 77.6 ± 4.6 years, 25 female [F]/17 male [M]) and 19 PiB(+) patients with AD (age = 63.1 ± 10.3 years, 12 F/7 M) over 1 to 3 years of follow-up. FTP change, structural MRI measures of atrophy, and cross-modal correlations were examined on a voxelwise level. Regional annual percentage change in FTP was also calculated. RESULTS: Voxelwise FTP change in AD showed the greatest increases in lateral and medial frontal lobes. Atrophy over the same interval was more widespread and included posteromedial cortical areas, where tau accumulation rates were lower. In OA, FTP binding increased in bilateral temporal lobe and retrosplenial cortex, accompanied by atrophy in the same regions. There were no associations between voxelwise change in FTP and sex, PiB, or APOE. Regional FTP significantly increased at follow-up in OA and patients with AD. Mixed effects models showed greater FTP increases in AD compared to OA, and no differences within OA based on PiB status. INTERPRETATION: Our findings indicate that tau accumulates even in amyloid-negative healthy OA and this process can be measured with in vivo tau-PET. In OA, tau accumulation and atrophy share a similar topography. In AD, tau increases more rapidly and accumulation occurs in frontal regions that are not yet undergoing significant atrophy.